Microarray Analysis of lncRNA and mRNA Reveals Enhanced Lipolysis Along With Metabolic Remodeling in Mice Infected With Larval Echinococcus granulosus - Lu, Yang; Liu, Hua; Yang, Xiao-ying; Liu, Jia-xue; Dai, Meng-yu; Wu, Jia-cheng; Guo, Yu-xin; Luo, Tian-cheng; Sun, Fen-fen; Pan, Wei (Frontiers in Physiology, 2020)
Parasitic infection improves metabolic homeostasis in “western diet”-induced obesity through the regulation of adipogenesis. However, the underlying mechanism is not yet fully understood. Using microarray analysis, this study investigated the long non-coding RNA (lncRNA) and messenger RNA (mRNA) profiles of subcutaneous adipose tissues from mice infected with Echinococcus granulosus protoscoleces. A total of 1052 mRNA (541 upregulated, 511 downregulated) and 220 lncRNA (126 upregulated, 94 downregulated) transcripts were differentially expressed (fold change ≥2, P < 0.05) in the infected subcutaneous adipose tissues. When compared with the control group, the infected mice showed a decrease in adipose tissue mass and a reduction in adipocyte size. Indirect calorimetry revealed the change in the energy metabolism after infection, characterized by a lower CO2 production and O2 consumption, a sharp decline in carbohydrate oxidation, and a slight increase in fat oxidation. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses showed that the parasitic infection reprogrammed a complex metabolic network. Notably, “lipoxygenase” and “arginine and proline metabolism” pathways were significantly upregulated while “glycolysis,” “tricarboxylic acid cycle,” “de novo lipogenesis,” and “lipid droplet” pathways were dramatically downregulated. In addition, several key lncRNAs were associated with insulin resistance and adipocyte differentiation. Overall, the present study suggested that E. granulosus infection could enhance lipolysis. Thus, our findings provide novel insights into parasite-mediated metabolic homeostasis, and into the mechanism of hypertrophic adipocytes in obesity.